Ideal de mujer virtuosa Instruida, sencilla, señora de la casa, pozo de dulzura y abnegación. Rastreos sobre la educación de la mujer a finales del siglo XIX y principios del siglo XX. (2014)
The lines inscribed on female education in the late nineteenth century and early twentieth centuries werecrossed, that began to circulate about knowledge (housekeeping, household, sewing and mending, manners,hygiene economic, political, cultural, educational and teaching interests... ) and that in turn gave way to anideal type of woman >> << virtuous framed in a "natural" must be a mother and wife. To achieve this idealcertain disciplinary practices that sought to channel the feelings and duties of girls were deployed; one of theauspicious scenarios this training was to feed the girls' school.However, those who sought the moral and good customs of the time (the prostitutes, workers, feminists who promulgated the doctrines and selfish mothers) were devoid of any sign of love and admiration; disapproved behaviors were silenced and their practices. Rather dye that Eva had caused the destruction of paradise.